A Method for Directly Observing Mechanical Oscillations in Photonic Structures Based on Porous Silicon Nanostructures - Miller Toledo Solano; Hector H. Cerecedo-Nuñez; Martha Alicia Palomino Ovando; Jocelyn Faubert; Khashayar Misaghian; J. Eduardo Lugo (Micro, 2024)
Due to their unique properties, porous silicon nanostructures have garnered much attention in photonics. For example, these structures can exhibit photoluminescence and are highly efficient in trapping light, making them ideal for applications such as biosensors, optical communication, and solar cells. The production of electromagnetic forces by light is a well-established concept, and the mechanism behind it is well-understood. In the past, we have used these forces to induce mechanical oscillations in a photonic structure based on porous silicon. Usually, to detect the oscillations, a high-precision vibrometer is utilized. However, we report a novel approach to visualizing photonic structure oscillations here. The traditional method of using a vibrometer as an indirect measurement tool has been replaced by one that involves directly observing the changes using a camera, digital movement amplification, a theoretical approximation, and FDTE simulations. This original technique provides researchers with a less expensive means of studying photonic structure movements. This proposal could be extended to other microscopic movements or for dynamical interferometric fringe analysis.